Immunorecognition and Neutralization of Crotalus durissus cumanensis Venom by a Commercial Antivenom Produced in Colombia (2022)
ABSTRACT: In Colombia, on average 2.9% of the nearly 5600 snakebite events that occur annually involve the rattlesnake Crotalus durissus cumanensis. The envenomation by this snake is mainly characterized by neurotoxicity and the main toxin is crotoxin (~64.7% of the total venom). The Instituto Nacional de Salud (INS) produces a polyvalent antivenom aimed at the treatment of bothropic, crotalid, and lachesic envenomations; nonetheless, its immune reactivity profile and neutralizing capacity over biological activities of the C. d. cumanensis venom has been poorly evaluated. In this sense, the study aims: (1) to describe an in-depth exploration of its immunoreactivity through second-generation antivenomics and HPLC fraction-specific ELISA immunoprofiles; and (2) to evaluate the neutralization pattern of the rattlesnake venom in vitro and in vivo biological activities. The results obtained showed a variable recognition of crotoxin subunits, in addition to a molecular mass-dependent immunoreactivity pattern in which the disintegrins were not recognized, and snake venom metalloproteinases and L-amino acid oxidases were the most recognized. Additionally, a high neutralization of proteolytic and coagulant activities was observed, but not over the PLA2 activity. Further, the median effective dose against C. d. cumanensis venom lethality was 962 µL of antivenom per mg of venom. In conclusion, (1) the antivenom recognition over the crotoxin and the disintegrins of the C. d. cumanensis should be improved, thus aiming upcoming efforts for the exploration of new techniques and approaches in antivenom production in Colombia, and (2) the neutralization activity of the antivenom seems to follow the molecular mass-dependent recognition pattern, although other explanations should be explored.